Khanza Hospital Information System and Outpatient Service Efficiency at Bhayangkara Brimob Hospital - Sofyan Dili Nurfitriadi; Suryarini Widodo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study analyzes the implementation of the Khanza Hospital ‎Management Information System in outpatient services at Bhayangkara ‎Brimob Hospital, Depok, and its contribution to perceived and process-‎based service efficiency. The field study was conducted in 2025 using a ‎descriptive qualitative design. Thirty-eight participants were selected ‎purposively: 29 main informants from registration, outpatient clinics, ‎pharmacy, cashier/finance, and information technology, and nine ‎triangulation informants in coordinating or supervisory roles. Data were ‎collected through guided in-depth interviews with open-ended questions, ‎direct observation, and document review. Interview recordings were ‎transcribed, organized by participant characteristics and work units, and ‎analyzed using five implementation dimensions—infrastructure, human ‎resources, standard operating procedures, supervision, and external ‎systems—together with recurring usability and technical issues. Findings ‎were strengthened through cross-source triangulation. Khanza supported ‎integrated information flow, electronic clinical documentation and ‎prescriptions, more structured pharmacy and financial processes, ‎improved data accessibility, and better inter-unit coordination. ‎Nevertheless, these benefits were constrained by dependence on a single ‎internet provider, non-uniform updates, software errors, interface ‎complexity, incomplete medical-device integration, data-entry errors, ‎and uneven supervision and user adoption. The study therefore ‎supports a positive contribution to perceived and process-based ‎outpatient efficiency rather than quantified economic or time efficiency. ‎Strengthening governance, role-based training, systematic monitoring, ‎network redundancy, usability, data validation, and interoperability is ‎recommended.